Histopathological study of endometrium in dysfunctional uterine bleeding - Loganathan, Malarvizhi; Krishnakumar, Meera (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study was undertaken to study the endometrial histology in patients presenting with abnormal uterine bleeding in the absence of palpable pelvic pathology, which helps in choosing the right modality of treatment in a particular age group with a specific histological change. The study of endometrium in dysfunctional uterine bleeding was undertaken to correlate clinical presentations with histopathological studies and to correlate the distribution of histopathological findings in various age groups. Methods: The present study was conducted in the Department of Obstetrics and Gynaecology at Govt. Dharmapuri Medical College and Hospital during the period 01.07.2017 to 31.05.2018. Patients presenting to Govt. Dharmapuri Medical College and Hospital with abnormal uterine bleeding form the material of this study. Cases have been selected by using purposive sampling technique. Results: An ovulatory cycles were more common than ovulatory cycles in all age group. However, in patients with menorrhagia and polymenorrhagia majority had secretory endometrium (ovulatory cycles). Conclusions: Majority of the patients were found in the reproduction age group with the maximum percentage in multiparous women. Menorrhagia was the commonest mode of presentation in all age group. Most of the patients with proliferative and secretory endometrium had normal sized uterus and normal looking endometrium.